Restoran Malinda / Nur Insyirah Mohammad … [et al.] - MOHAMMAD, NUR INSYIRAH; FAISAL, A'QILAH A'RIFAH; ABD RASID, WARDAH ZAHIRAH (2019)
This is the case study of Restoran Malinda. From this research it is found that, Restoran Malinda faces several problems which are poor order system, lack of advertisement and promotion and limited quantity of produced. Therefore, we comes out with the technological based solution to improve these problems.